Novel patterned layer to enhance conversion efficiency of amorphous silicon thin‐film solar cells. Issue 7 (6th March 2014) - Kim, Yang Doo; Han, Kang‐Soo; Shin, Ju‐Hyeon; Cho, Joong‐Yeon; Im, Chan; Lee, Heon
<x xml:space="preserve">Abstract</x> The substrate of an a‐Si:H solar cell with microscale surface roughness generally shows high diffuse transmittance; however, it also has detrimental effects, including low open‐circuit voltage and fill factor (FF). We applied planarization to the rough surface using spin‐coating of ZnO nanoparticles dispersed in an ethanol‐based solution. The resulting conversion efficiency of the solar cell increased by ∼18% owing to the higher open‐circuit voltage and FF, with a small decrease in the diffused transmittance.